Frontal sinus obliteration with beta-tricalcium phosphate putty: case series with long-term radiological follow up. Issue 2 (20th February 2023) - Moore, P; Kam, J K T; Castle-Kirszbaum, M; Tan, D; Wreghitt, S; Lee, S; Gonzalvo, C A
Abstract: Objectives: Frontal sinus obliteration is often performed using fat, autologous bone or a range of synthetic materials. This paper reports the long-term clinical and radiological outcomes of frontal sinus obliteration using beta-tricalcium phosphate putty. Methods: A retrospective audit was performed of patients who underwent frontal sinus obliteration with beta-tricalcium phosphate putty. Patient-, disease- and procedure-related data were collected. Pre- and post-operative computed tomography scans were reviewed to assess bone integration. Results: Four patients underwent frontal sinus obliteration using beta-tricalcium phosphate putty for treatment of a cerebrospinal leak, mucocele and recalcitrant frontal sinusitis. All patients had disease resolution, with no intra- or post-operative complications reported in the 16.5-month follow up. Post-operative computed tomography scans confirmed native bone obliteration of the frontonasal ducts in all patients. Conclusion: Beta-tricalcium phosphate putty is a safe and effective option for bone obliteration of the frontal sinus in a range of pathologies, including cerebrospinal fluid leak.